Pendugaan gaya penarikan bajak singkal lokal menggunakan bajak pahat (draught prediction of local made mouldboard plow using a tine - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
An investigation to predict the draught required by local made mouldboard plow was conducted. A methodology was developed based upon an existing force prediction model which describes the draught of tine as the product of two factors, related to soil strength and tool geometry respectively. The experiments were conducted in a two steps,â¢ involving (1) establishing, in a reference soil, some comparative draught relationship (tool index, I) between each of local made mouldboard plows and the standard tine over a range of plowing depths, and (2) measuring the draught of standard tine and local made mouldboard plows in field. The methodology was validated in three field soil conditions. The results showed that the local mouldboard plows index (I) could be described as three order of polynomial equation based on its plowing depth (d). In the three field soil condition, the average prediction error for mouldboard plows from Sleman, Gunungkidul, Kulonprogo, Purworejo, and Cilacap were 10.08%, 18.76%, 12.59%, 10.58%, and 12.26% respectively. The lowest error value was 8.54% and the highest error value was 25.63 . Key word : plow index, draught prediction, mouldboard plow, standard tine